UPAYA PENINGKATAN KETERAMPILAN SOSIAL DALAM EKOLITERASI KETAHANAN HAYATI MELALUI PEMBELAJARAN KOOPERATIF TIPE KELOMPOK INVESTIGASI PADA MAHASISWA PENDIDIKAN BIOLOGI SEMESTER III TAHUN AKADEMIK 2008/2009 - Ni Wayan Ekayanti; Dewa Ayu Puspitawati; Sang Putu Kaler Surata (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2011)
Environmental damage that has occurred recently, caused a various biosecurity problems. However, the people knowledge, understanding and awareness about these are still low. The ecoliteracy is a strategic approach for enggaging young generation in manage biosecurity issues. The purpose of this study is to evaluate how far undergraduate teacher training students able to increase their social skill, as one important aspect for successful management of biosecurity, after following biosecurity ecoliteracy. It was excecuted through class action research toward 30 undergraduate students of Biology Education Department, University of Mahasaraswati Denpasar. They followed indoor and outdoor learning based on cooperative learning approach and group investigation techniques nearly two month (August-September 2009), with twice face to face interaction in a week. Their behavior were observed using a rubric with four Likert Scalle, and data was analyzed with z-test. Nearly all components social skill of students were increasing significantly: contribution to group objectives (P =0.000), contribution to group knowledge (P=0.000), and sharing ideas (P=0.000). These showed that cooperative learning and group investigation are strongly tool for encouraging social skill in biosecurity ecoliteracy.